Pengaruh Total Asset Turnover (TAT) dan Kualitas Aktiva Produktif (KAP) Terhadap Profitabilitas (ROA) dengan Non Performing Financing sebagai Variabel Moderasi pada Bank Umum Syariah di Indonesia Periode 2019-2023 - Yulpida Sari Lubis; Imsar Imsar; Laylan Syafina (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This study aims to find out how the Effect of Total Asset Turnover (TAT), Quality of Productive Assets (KAP) on Profitability (ROA) with Non-Performing Financing (NPF) as a Moderating Variable in Sharia Commercial Banks in Indonesia for the Period 2019 - 2023 The independent variables used are TAT and KAP, the dependent variables used in this study are Profitability (ROA) and moderation variables in the form of NPF. The research data used is secondary data, TAT level, KAP level and also profitability level (ROA) and is obtained from the official website of each Sharia Commercial Bank in Indonesia which has been published at the Financial Services Authority (OJK). Namely this research consists of 30 data where the data used is the annual data of Islamic commercial banks in Indonesia. The research method used in this study is quantitative with a descriptive approach. The analysis techniques used in this study are partial test (t-test), simultaneous test (F-test), determination coefficient test (R2) and MRA analysis test using SPSS Version 25.00 analysis tool. The results showed that the TAT variable had no effect on ROA. The KAP variable has a positive and significant effect on ROA. The variables KAP and TAT have a simultaneous effect on ROA. The NPF variable is not able to moderate the effect of TAT on ROA. The NPF variable is not able to moderate the effect of KAP on ROA.